SOS Titanic - Bunting, Eve, 1928- (new york scholastic, 1996)
Fifteen-year-old Barry O'Neill, traveling from Ireland to America on the maiden voyage of the Titanic, finds his life endangered when the ship hits an iceberg and begins to sink.
G4
Keywords: Titanic (Steamship) -- Juvenile fiction; Titanic (Steamship) -- Fiction; Ocean liners -- Fiction; Shipwrecks -- Fiction; Historical fiction; Sea stories